Post-Operative Drop in Hemoglobin and Need of Blood Transfusion in Cesarean Section at Dhulikhel Hospital, Kathmandu University Hospital - Singh, B; Adhikari, N; Ghimire, S; Dhital, S (Kathmandu University Medical Journal, 2015)
Background Cesarean section has been identified as one of the commonest indication for blood transfusion in obstetric practice because it involves risk of major intra-operative blood loss. Different figures varying from less than 500 ml to more than 1000 ml have been quoted as estimated blood loss associated with caesarean section. There is also a wide variation in blood ordering practices for this surgery. Objective The objective of this study is to evaluate the blood ordering practice and transfusion for cesarean sections at our institute, to see post-operative drop in hemoglobin and hematocrit and to correlate those parameters with the duration between uterine incision and repair. Methods In this prospective observational study, non-randomised purposive sample was taken from 121 ladies who underwent elective and emergency cesarean section at the department of obstetrics of Dhulikhel Hospital-Kathmandu University Hospital. Post-cesarean drop in hemoglobin and hematocrit and their relation with duration of uterine manipulation was calculated. Cross-match to transfusion (C/T ratio) ratio, transfusion probability (%T) and transfusion index (Ti) were also calculated. Results Most frequent blood group was found to be O positive (38%) among those ladies. Average post-cesarean drop in hemoglobin was 1.52±1.27 gm/dl and drop in haematocrit was 5.49±4.1%. Post-operative drop in hemoglobin and haematocrit had weak and positive linear relation with duration between uterine incision and repair. Cross-match to transfusion ratio was 1, transfusion probability 100% and transfusion index was 2. Conclusion There is no need of routine cross-matching of blood for cesarean section. Only grouping with confirmation of availability should be done for emergency situation. DOI: http://dx.doi.org/10.3126/kumj.v11i2.12490 Kathmandu University Medical Journal Vol.11(2) 2013: 144-146